2006
DOI: 10.1007/s10495-006-3979-8
|View full text |Cite
|
Sign up to set email alerts
|

A novel isoform of prostate apoptosis response 4 (PAR-4) that co-distributes with F-actin and prevents apoptosis in neural stem cells

Abstract: The elevated expression of prostate apoptosis response-4 (PAR-4) induces apoptosis in differentiating mouse embryonic stem (ES) cells. In embryoid body (EB) cells and the E15.5 stage of embryonic mouse brain, PAR-4 is expressed as two isoforms (38 and 33 kDa). Using mouse EB-derived RNA as a template we have cloned and characterized a novel isoform of PAR-4 (PAR-4/p33) that lacks exon 3 and shows a bona fide splice junction of exons 2 and 4. The molecular mass for PAR-4/p33 is estimated to be 33 kDa, correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…It is critical for tumor suppression by inducing apoptosis [109-112]. In subsequent studies, we found that ceramide promotes binding of aPKC to PAR-4, which suppresses activation of cell survival pathways such as NF-kB by aPKC in pluripotent stem cells [22, 26, 113]. When stem cells further differentiate to NPCs, PAR-4 expression is downregulated, which renders these cells insensitive to ceramide-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is critical for tumor suppression by inducing apoptosis [109-112]. In subsequent studies, we found that ceramide promotes binding of aPKC to PAR-4, which suppresses activation of cell survival pathways such as NF-kB by aPKC in pluripotent stem cells [22, 26, 113]. When stem cells further differentiate to NPCs, PAR-4 expression is downregulated, which renders these cells insensitive to ceramide-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it may be of interest that PAR-4 has been found to be temporarily associated with the actin cytoskeleton [136] . Our group has described a short form of PAR-4 that acts as dominant negative regulator of apoptosis by forming actin-associated heterodimers with the pro-apoptotic long form of PAR-4 [6] .…”
Section: Lipid Rafts and Slips: A Platform For Cell Signaling Pathwaysmentioning
confidence: 99%
“…For example, if cells express high levels of prostate apoptosis response 4 (PAR-4), an inhibitor protein of aPKC, ceramide will induce binding of PAR-4 to aPKC. PAR-4-mediated inhibition of aPKC will then result in apoptosis [2,[4][5][6] . If cells express low levels of PAR-4, ceramide will promote association of the small GTPase Cdc42 with aPKC and sustain cell polarity [3] .…”
Section: Introduction and Overviewmentioning
confidence: 99%
“…It was also known that aPKC interaction with an endogenous inhibitor protein, prostate apoptosis response-4 (PAR-4) previously discovered in prostate cancer cells, induces apoptosis [123–125]. We demonstrated for the first time that ceramide activates and enhances autophosphorylation of aPKC in cells, but also induces inactivation of aPKC when PAR-4 expression is elevated [108, 111, 126129]. Moreover, we showed that this mechanism (sensitizing cells to ceramide by expressing PAR-4) eliminates teratoma (stem cell tumor)-forming stem cells from differentiating ES cells and may also control the number of neural progenitors during brain development [126, 128].…”
Section: Lipid Mediators That Affect Protein Kinase Cascades and Ementioning
confidence: 96%